Canon EOS Rebel T5/1200D for dummies - King, Julie A.; Correll, Robert (--For dummies., 2014)
Presents a guide to the Canon EOS Rebel T5/1200D camera that explains its basic features and provides advice for manipulating settings for exposure, focus, depth of field, color, and shooting movies.